Perceptions and Attitude of Registered Nurses Towards Professionalism in Nursing from Selected Hospitals of Guntur District, Andhra Pradesh: A Comparative Study - B. Nirmala Jyothi; Mulpur Vasantha; A. Suneetha; Ch. Venkateswarlu (International Journal of Evidence Based Nursing And Practices, 2023)
Background: Nursing professionalism refers to a collection of principles that are essential to raising the standard of patient care while enhancing the methodology, norms, and judgement that direct nursing activities on a daily basis. The main objective of the study is to assess the perceptions and attitude of registered nurses towards professionalism in nursing. Materials and Methods: A comparative descriptive research design adopted for this study. The study conducted at selected hospitals in Guntur and Mangalagiri. Seventy-five participants of public hospitals registered nurses, 75 participants of private hospitals registered nurses selected by using random-sampling technique. A structured questionnaire used to collect the sociodemographic data and standardized Likert-type scales used to assess the perceptions and attitude in professionalism in nursing. Results: The study results shown majority 41 (54.6%) of the public hospital register nurses were had B.Sc. Nursing and private hospital registered nurses 42 (56%) were had Diploma/GNM, and 30 (40%) of the public hospital register nurses having 6 to 10 years, where in private hospital registered nurses the majority 29 (38.6%) were having less than 5 years of experience. There was a significant difference between perceptions and attitude among public and private hospital nurses regarding professionalism. Conclusion: The study concluded that the registered nurses working in public hospital were having superior perceptions and attitude than registered nurses working in public hospital.
Keywords: Hospital; Nursing; Perceptions; attitude; nurses; professionalism; registered nurses